Psicopatia e reconhecimento de faces emocionais em presidiárias - Salvador-silva, Roberta (2014)
BACKGROUND: Psychopaths show impairments in emotional processing. Data about their ability to recognize emotional faces are not convergent. Prior studies revealed a lack of methodological convergence, in particular in relation to the exposure time of the stimuli, and on the sex bias of the sample with the majority of the studies focusing on male participants. This thesis aimed to investigate characteristics of psychopathy in female offenders, consisting of two empirical studies. The first study aimed to verify the recognition of facial expressions of emotion in psychopaths, being the first study to test the control of exposure time of 200 ms in the female sample. The second study investigated whether, in the same sample, psychopathy is isomorphic to Antisocial Personality Disorder (APD) or if a discriminative pattern of scores on APD criteria is observed. METHOD: 109 female offenders from Porto Alegre city Brazil were evaluated and, based on the PCL-R and SCID-II scores, three groups were formed: 1) female psychopathic inmates (PCL-R ≥ 30; n=33); 2) female antisocial (APD) non-psychopathic inmates (PCL-R < 20, n=43); and 3) female inmates without any personality disorder (control group) (PCL-R < 10, n=33). In the first study, participants completed a facial affect recognition task. In the second study, we used Latent Class Analysis based on the scores of the same measures to check whether psychopathy distinguishes between latent class female offenders with clinical diagnosis of APD. RESULTS: The first study revealed significant deficits in negative emotions (fear, sadness and disgust) in the psychopathic group, with the highest effect size being observed in processing of fear precisely when the stimuli were presented in 200 ms. Deficits were also observed in the APD group to the emotion of fear and disgust in shorter exposure times compared to the control group. In the second we identified three latent class with varying degrees of APD. Participants with a clinical diagnosis of APD fell into two latent class with significantly different mean scores on PCL-R psychopathy. Females with PCL-R total scores ≥ 30 fell almost exclusively within the Severe APD class; the Moderate APD class had almost no individuals with a PCL-R total score ≥ 30. CONCLUSION: The present work corroborates the data about the impairments in facial emotion recognition in psychopaths with unprecedented results in the literature for female samples. Data confirm that the more specific deficits shown by psychopaths are only observed in a reduced exposure time experimental stimulus. Moreover, we found novel empirical evidence that female offenders with clinical APD comprise a heterogeneous population, as higher levels of psychopathy only occurred in a subset of women above the clinical threshold for APD.